Application of FVSI, Lmn and CPF Techniques for Proper Positioning of FACTS Devices and SCIG Wind Turbine Integrated to a Distributed Network for Voltage Stability Enhancement - Eisa Osman, S. H.; Irungu, G. K.; Murage, D. K. (Engineering, Technology & Applied Science Research, 2019)
Induction power generators are the most popular wind energy conversion systems (WECS) because they do not require synchronization units. However, they usually draw a huge quantity of reactive power during disturbances. Hence, incorporating wind power into power networks may cause voltage instability. This paper presents the usage of STATCOM and SSSC FACTS devices for voltage stability enhancement of a distribution network with a squirrel cage induction generator (SCIG) wind power turbine. The continuation power flow (CPF) approach is utilized as a tool to determine the most suitable position of SCIG in the system. Also, voltage stability indices (FVSI and Lmn) are employed to estimate the stability margin of the system by figuring the weakest transmission lines and buses in order to locate the appropriate position where the FACTS devices should be installed. A comparison of the suitability of the FACTS devices to restore system stability was evaluated under 3-phase fault conditions. The results illustrated that STATCOM behaves better than SSSC when the system is restoring from a fault. Simulations and voltage stability assessment were carried out on the IEEE 14 bus test scheme using the PSAT simulation software package.